Evaluation of local potential-based local marine biology field practicum program - Nur Fitriana Sam; Nursia Nursia; Permadi Burhanuddin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Marine biology field practicum based on local potential is routinely held at the Department of Biology Education, Faculty of Teacher Training and Education, University of Borneo Tarakan, but has never been evaluated. This study aims to analyze the implementation and results of the field practicum that has been carried out, and make decisions so that the quality of the process and output of the practicum can be increased. This research is an evaluation research using countenance stake model which is qualitative in nature. The unit of analysis used is the course lecturer, students, field assistants, head of the laboratory, study program curriculum, lesson plans, infrastructure, tools and materials, practicum guides, and practicum reports. The techniques used are observation, interviews and document analysis. Data were analyzed using data condensation techniques, data presentation, and data verification. The results of this study are: 1) the planning stage is of poor quality, 2) the process (transaction) stage is of good quality, and 3) the product (outcomes) stage is of excellent quality. The team of lecturers supporting the course needs to plan practicums more carefully as an effort to improve, such as revising the RPS, compiling practicum guidelines based on local potential, compiling assessment instruments and coordinating well with the head of the laboratory regarding the practicum implementation.AbstrakPraktikum lapangan biologi laut berbasis potensi lokal rutin dilaksanakan pada jurusan Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Borneo Tarakan, namun belum pernah dievaluasi. Penelitian ini bertujuan untuk menganalisis pelaksanaan dan hasil praktikum lapangan yang telah dilaksanakan, dan membuat keputusan agar kualitas proses dan keluaran praktikum dapat meningkat. Penelitian ini merupakan penelitian evaluasi menggunakan model countenance stake yang bersifat kualitatif. Unit analisis yang digunakan adalah Dosen Pengampuh mata kuliah, Mahasiswa, Pembantu Lapang, Kepala Laboratorium, kurikulum prodi, RPS, sarana prasarana, alat dan bahan, panduan praktikum, dan laporan praktikum. Teknik yang digunakan yaitu observasi, wawancara dan analisis dokumen. Data dianalisis menggunakan teknik kondensasi data, penyajian data, dan verifikasi data. Hasil dari penelitian ini yaitu: 1) tahap perencanaan berada pada kualitas kurang baik, 2) tahap proses (transaction) berada pada kualitas baik, dan 3) tahap produk (outcomes) berada pada kualitas sangat baik. Tim Dosen pengampuh mata kuliah perlu merencanakan praktikum dengan lebih matang sebagai upaya perbaikan, seperti merevisi RPS, menyusun panduan praktikum berbasis potensi lokal, menyusun instrumen penilaian dan melakukan koordinasi yang baik dengan kepala laboratorium terkait pelaksanaan praktikum.